Strengthening of structures using brick inserts to reduce the captive column effect during earthquake - Babu, R. Suresh; Venkatasubramani, R.; Venkatasubramani, G. S. (Journal of Structural Engineering, 2025)
Masonry infilled panels are normally used as partitions or as architectural elements in Reinforced Concrete (RC) structures. During the erection of the windows or ventilators, the infill cannot be completely filled in the panels of RC frames. This forms only a partial infill. If the infill panel is built shorter with a gap, the adjacent columns are unable to flex under the lateral loads during an earthquake due to in-plane stiffness of the infills. They behave as short columns and can be seriously damaged during an earthquake due to excessive shear forces. This behaviour is called captive column effect. RC framed buildings with infill walls are usually analysed and designed as bare frames without considering the strength and stiffness contributions of the infills. On the other hand, the real behaviour of the structure with partial infill walls during an earthquake is like a captive column. To avoid failure due to captive column effect in the existing RC frame building with partial infill, masonry inserts are normally recommended as remedy to obtain diagonal strut behaviour in the masonry to make the shear flow smooth. An experimental investigation was carried out to study the effect of lateral behaviour of RC frames with partial-infill masonry panels. This study clearly indicates that the partial infill in RC frame leads to critical damages, which could be reinforced with masonry inserts and this provision of brick inserts improves the lateral capacity by way of reducing the captive column effect for seismic load.